Tai Chi Chuan and Qigong in Primary Health Care: a qualification case - Soares, Amanda Nathale; Lacerda e Silva, Thais; Jorge Maciel, Fernanda; Alves de Andrade Melo Franco, Adriana; de Souza Carvalho José, Camile; Salles Giffoni, José Marcello; Oliveira de Lima, Kelly Cristina; Souzalima Campos, Daniela; Souza Oliveira, Paula; Quintela Zanette Reis, Bárbara; Pereira de Sousa, Marilene; Vianna de Rezende, Waleska Aparecida; et al. (Cadernos ESP, 2026)
Objective: describe the educational initiative “Body Practices in Health Academy Centers of Minas Gerais State (Brazil): qualifying Tai Chi Chuan and Qigong trainers.” Methods: this is an experience report of 12 cohorts between 2023 and 2025 through a partnership among the Minas Gerais State School of Public Health, the Federal Institute of Minas Gerais – Sabará Campus, and the Minas Gerais State Department of Health. Results: a total of 316 professionals from 173 municipalities enrolled. Most participants were women aged 30-44 years, with undergraduate degrees in Physical Education. Challenges regarding municipal management support for professional participation and for increase body practices at the participating municipalities were observed. Conclusions: the Continuing Health Education paradigm supported context-based learning and facilitated the incorporation of body practices into participating municipalities.
Keywords: Tai Ji; Qigong; Complementary Therapies; Unified Health System; Permanent Education